Changes in the incidence and prevalence of rheumatoid arthritis in Kamitonda, Wakayama, Japan, 1965–1996. Issue 12 (1st December 1999) - Shichikawa, Kanji; Inoue, Koji; Hirota, Shigenaga; Maeda, Akira; Ota, Hiroshi; Kimura, Masami; Ushiyama, Toshio; Tsujimoto, Masaki
Abstract : OBJECTIVE: To evaluate secular trends in the incidence and prevalence of rheumatoid arthritis (RA) in Japan. METHODS: The incidence and prevalence of RA were determined in a longitudinal population based study in the Kamitonda district, Wakayama, Japan, from 1965 to 1996. RESULTS: In the study area consisting of about 3000 inhabitants, 16 incident cases, satisfying definite RA by the Rome criteria were detected during the study period. The age and sex adjusted incidence in both men and women combined and the age adjusted incidence in women significantly decreased (p<0.025 and p<0.01, respectively). The age and sex adjusted prevalence in all inhabitants tended to decrease (p<0.1), and the age adjusted prevalence in women significantly declined (p<0.025). In men, however, neither incidence nor prevalence showed significant change. CONCLUSIONS: The decline of incidence and prevalence of female RA may be reducible to some environmental changes preferentially occurring more obviously in Japanese women than in men. Because the use of oral contraceptives has been extremely low in Japan, the decline should be explained by other factors.